24 - Klaus Abbink; Jordi Brandts (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2003)
Bertrand competition under decreasing returns involves a wide interval of pure strategy equilibrium prices. We first present results of experiments in which two, three and four identical firms repeatedly interact in this environment. Less collusion with more firms leads to lower average prices. With more than two firms, the predominant market price is 24, a price not predicted by conventional equilibrium theories. This phenomenon can be captured by a simple imitation model and by a focal point explanation. For the long run, the model predicts that prices converge to the Walrasian outcome. We then use data from three new treatments to properly test the imitation model against the focal point notion.
Keywords: C90; C72; D43; D83; L13; 330; Laboratory experiments; industrial organisation; oligopoly; price competition; co-ordination games; learning; Oligopol; Preiswettbewerb; Spieltheorie; Imitationswettbewerb; Theorie